Translation and validation of the premenstrual change coping inventory in Indonesian version - Susanti, Henny Dwi; Rikawati, Rintan; Yunitri, Ninik; Kustanti, Christina Yeni (Pediomaternal Nursing Journal, 2025)
Introduction: Premenstrual syndrome (PMS) affects millions of women worldwide, characterized by physical and psychological symptoms that occur cyclically before menstruation. In Indonesia, understanding and managing PMS remains challenging due to social stigma and lack of awareness. The Premenstrual Change Coping Inventory (PMS-Cope) is a validated tool designed to measure mental strategies used to adapt to menstrual cycle changes. However, no validated Indonesian version exists, creating a significant gap in research and clinical practice for Indonesian womens. The research evaluated the translation and validation of the premenstrual change coping inventory (PMS-Cope) in Indonesia. Methods: 321 Indonesian women were included in this study. PMS-Cope used Cronbach's alpha and convenience sampling. Exploratory factor analysis (EFA) was used in this study to determine factor structure and evaluate the structural model fit. Confirmatory factor analysis was also used in this study. Results: The Cronbach's alpha value for the study was .90 overall. The CFA results for this study showed goodness of fit. The comparative fit index was .91, the related fit index (RFI) was .80, and the normed fit index was .83. The value of the Kaiser–Meier–Olkin test was .873, and Bartlett’s test value of sphericity was statistically significant and indicated adequate EFA. Conclusion: The result of this study showed that the PMS-Cope has satisfactory reliability and validity for evaluating PMS-cope in Indonesia. Keywords: premenstrual syndrome; translation; validation; women